Human Resource Management Strategy In Maintaining And Improving Employee Performance - Suhairi Suhairi; Rendi Setiawan Purba; Zamzami Akromi Lubis; Muhammad Sandi; Irgi Iqbal (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
Human resources (HR) is one of the most important assets for any organization. Good employee performance directly contributes to the company's success in achieving goals and gaining competitive advantage. However, in today's increasingly complex and dynamic business environment, companies are faced with increasingly difficult challenges in maintaining and improving employee performance. Factors such as global competition, technological advances, demographic changes, and ever-evolving market dynamics have changed the business landscape. Companies are required to develop effective human resource management strategies to ensure that employees have the appropriate skills, knowledge and motivation to achieve competitive advantage. The purpose of this study is to determine the strategy that will be used by human resource management to maintain and improve employee performance. This research method uses a qualitative descriptive analysis method, by critically examining it using library research methods. The results of the study show that human resource managers (HR) must stay up-to-date with the given strategy and adhere to the theory to support the success of an organization or company, namely planning, developing, monitoring, and motivation are the keys to the success of an organization or company.